Taxonomic and phylogenetic relationships between neotropical species of ticks from genus Amblyomma (Acari: Ixodidae) inferred from second internal transcribed spacer sequences of rDNA - Marrelli, M. T.; Souza, L. F.; Marques, R. C.; Labruna, M. B.; Matioli, S. R.; Tonon, A. P.; Ribolla, P. E M [UNESP]; Marinotti, O.; Schumaker, T. T S (My University, 2007)
The accurate specific identification of ticks is essential for the study, control and prevention of tick-borne diseases. Herein, we determined ribosomal nucleotide sequences of the second internal transcribed spacer (ITS2) of 15 Neotropical hard tick species of the genus Amblyomma Koch found in Brazil. Most of the studied ticks accidentally parasite humans and potentially act as vectors of zoonoses. Lengths of the ITS2 sequences ranged from 956 to 1,207 bp, whereas GC content varied from 62.4 to 66.9%. A matrix of ITS2 divergence was calculated with the ITS2 sequence data obtained showing divergence levels varying from 1.5 to 28.8%. The analysis indicated that this molecular marker can be useful for Amblyomma-specific identification. Phylogenetic inferences based on the ITS2 sequences were used to assess some issues in subgenus taxonomy. © 2007 Entomological Society of America.
Keywords: Amblyomma; ITS2; Phylogeny; Taxonomy; Ticks; primer DNA; ribosomal spacer DNA; animal; animal disease; Brazil; chemistry; classification; comparative study; DNA sequence; genetics; molecular genetics; nucleotide sequence; phylogeny; polymerase chain reaction; sequence homology; species difference; tick; Animals; Base Sequence; DNA Primers; DNA, Ribosomal Spacer; Ixodidae; Molecular Sequence Data; Polymerase Chain Reaction; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; Species Specificity; Acari; Ixodida